Biological rhythms in the deep-sea hydrothermal mussel Bathymodiolus azoricus - Audrey M. Mat; Jozée Sarrazin; Gabriel V. Markov; Vincent Apremont; Christine Dubreuil; Camille Eché; Caroline Fabioux; Christophe Klopp; Pierre-Marie Sarradin; Arnaud Tanguy; Arnaud Huvet; Marjolaine Matabos (Nature Communications, 2020)
Little is known about gene expression of organisms in the deep sea, partially owing to constraints on sampling these organisms in situ. Here the authors circumvent this problem, fixing tissue of a deep-sea mussel at 1,688 m in depth, and later analyzing transcriptomes to reveal gene expression patterns showing tidal oscillations.